THE IMPACT OF INSTITUTIONAL QUALITY ON ECONOMIC GROWTH: A COMPARATIVE ANALYSIS OF THE EU AND NON-EU COUNTRIES OF SOUTHEAST EUROPE - Radulović, Marija (Economic Annals, 2020)
The quality of institutions and its impact on economic growth has become more important in recent years, especially in transition countries that must reform their institutions to create a mar-ket economy and meet the preconditions for joining the EU. This is the case with the countries of Southeastern Europe, some of which are already EU members, while oth-ers are in the process of joining the EU. This paper examines the effects of institutional quality on the economic growth of South-East Europe and compares these effects in EU and non-EU countries for the period 1996–2017, using Worldwide Governance Indicators (WGI) to measure the quality of institutions and the GDP growth rate. The panel autoregressive distributed lag (ARDL) approach is used to analyse the relationship between institutional quality and economic growth. The results show that in EU countries there is a long-run relation-ship between institutional quality and eco-nomic growth for all significant variables, while in the non-EU countries only govern-ment effectiveness, political stability and absence of violence, regulatory quality, and voice and accountability are statistically significant. Furthermore, in EU countries there is no short-run relationship between institutional quality and economic growth, while in the non-EU countries of SEE, regu-latory quality and voice and accountability are significant.